PENGARUH PELATIHAN SIKLUS AKUNTANSI PERUSAHAAN JASA DAN IMPLEMENTASI SIA BERBASIS KOMPUTER TERHADAP KINERJA BENDAHARA - Liantiningsih, Stefina Endang (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aimed to analyze the effect of the accounting cycle training for service companies, and implementation of computer-based SIA on the performance of the treasurer. The sampling technique used purposive sample. The number of samples taken from the entire population of as many as 30 people across the Association Dharmaputri school treasurer who has followed the accounting cycle training for service companies. Collecting data using a structured questionnaire and observation. Data were analyzed using multiple linear regression. The results showed that the accounting cycle training and implementation services company SIA-based computer partially and simultaneously have a significant influence and positive impact on the performance of the treasurer